Effect of organic and inorganic additives in membrane composition on the properties and performance of nanofiltration membrane for xylose and glucose separation - Nur’amirah, Abdul Ghafar (2015)
World production of biomass is estimated at 146 billion tons a year. The biomass resources can be used to meet variety of needs such as energy needs and food industries. Xylose and glucose are among the most abundant component that can be found in the biomass source. The purpose of the separation of xylose from glucose is to fully utilize the sugar component from the biomass source. Recent studies have found that nanofiltration (NF) method is possible for separation of xylose and glucose. Compared to the chromatography process, NF membrane is simple process, cost-effective and easy-maintenance. The objective of this study is to study the effect of organic and inorganic additives in membrane composition on the properties and performance of NF membrane for xylose and glucose separation. PES polymer is used in a casting solution with N-Methyl-2-pyrrolidone (NMP)as a solvent, PEG-200 and zinc chloride (ZnCl2) as an additive to the solution. The membrane performance of the membrane is investigated by varying 2 different types of additives with concentration that is 2 wt. %, for PEG-200 and 2 wt. % for zinc chloride. Membrane performance test was carried out with dead end filtration test by using Amicon Millipore stirred cell (Model 8200) with constant stirring speed at 300 rpm and temperature at ambient. Refractometer was used to analyse the samples concentration from separation process.It is found from the developed membrane, the addition of additives shows decreases in flux and the membrane permeability. The membrane type also changes from NF to RO range as organic additives and inorganic additives are mixed together. The membranes also have 99% rejectionfor both xylose and glucose and separation factor of xylose from glucose is almost 1. From the separation factor it shows that the membrane cannot separate the xylose from glucose. From the pore radius calculation it is found that the membrane pore size is in average 0.3 nm for all membrane had become one of the reason xylose cannot separated as its radius bigger than the pore size and xylose cannot pass through the membrane.